Education and the nation state : the selected works of S. Gopinathan - Gopinathan, Saravanan. (World library of educationalists series, 2013)
"In the World Library of Educationalists series, international experts themselves compile career-long collections of what they judge to be their finest pieces - extracts from books, key articles, salient research findings, major theoretical and practical contributions - so the world can read them in a single manageable volume. In a career spanning four decades, S. Gopinathan is considered by many to be a pillar of teacher education in Singapore. He has played a key role in the establishment and transformation of Singapore's education system, pioneering many programmes and advising on policy both nationally and internationally. In the process, he has contributed over 25 books (authored, co-authored and edited) and 115 articles and book chapters to the field, and continues to inspire and empower younger colleagues in the region to challenge the cause for excellence in education and education reform. In Education and the Nation State, S. Gopinathan brings together 14 of his key writings in one volume. Starting with a specially written introduction, which gives an overview of Gopinathan's career and contextualises his selection, the essays are then arranged thematically, providing an overview not just of his own career, but also reflecting the development and key concerns of education in the nation state that is Singapore"--